设f(x)=ln(x+1),(x>-1) (1)讨论函数g(x)=af(x)-
(2)求证:(1+
|
(1)g′(x)=-
,令x2+x-a=0,x2+x-a x+1
∵△=1+4a>0,∴g′(x)=0有两根,设为x1与x2且x1<x2,
x1=
,x2=-1- 1+4a 2
,-1+ 1+4a 2
当a≥0时x1≤-1,x2≥0,
∴当a≥0时g(x)在(-1,x2)上递增,在(x2,+∞)递减.
(2)原命题等价于证明ln(1+
)+ln(1+1 1
)+ln(1+1 2
)+…+ln(1+1 3
)<1 n
,n+2 2
由(1)知2ln(1+x)-
x2≤2ln2-1 2
,∴ln(x+1)≤1 2
x2+(ln2-1 4
),1 4
令x=
,得ln(1+1 n
)≤1 n
•1 4
+ln2-1 n2
,1 4
所以ln(1+
)+ln(1+1 1
)+ln(1+1 2
)+…+ln(1+1 3
)≤1 n
(1+1 4
+1 22
+1 32
+…+1 42
)+(ln2-1 n2
)n1 4
<
(1+1 4
+1 1×2
+1 2×3
+…+1 3×4
)+(ln2-1 (n-1)n
)n=1 4
(2-1 4
)+(ln2-1 n
)n<1 4
+(ln2-1 2
)n,1 4
只需证ln2-
<1 4
即可,即ln2<1 2
,3 4
∵ln2=ln
=ln4 24
,4 16
=lne3 4
=ln3 4
=ln4 e3
=ln4 2.73
,4 19.68
∴ln2<
,∴3 4
+(ln2-1 2
)n<1 4
<n+1 2
,n+2 2
∴ln(1+
)+ln(1+1 1
)+ln(1+1 2
)+…+ln(1+1 3
)<1 n
,n+2 2
∴(1+
)(1+1 1
)(1+1 2
)…(1+1 3
)<e1 n
.n+2 2